ANALISIS PROFIL KEMAMPUAN ARGUMENTASI ILMIAH SISWA SMP BERDASARKAN TOULMIN’S ARGUMENT PATTERN (TAP) - Fakhressy, Fanya; Susiyawati, Enny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the profile of junior high school students’ scientific argumentation skills based on Toulmin’s Argument Pattern (TAP) and the level of argumentation achieved. The study employs a quantitative, descriptive approach. The research subjects were 32 seventh-grade students at SMP Negeri 63 Surabaya, selected through purposive sampling. The research instrument consisted of a contextual phenomenon-based essay test designed based on TAP indicators. The results showed that students’ scientific argumentation skills were still very low, characterized by a dominance of Level 1 at 75%, while only 19% of students reached Level 2 and 6% reached Level 3. Based on the indicators, students were able to present a Claim (81.25%), Ground (71.88%), Warrant (40.63%), and Backing (9.38%). These findings indicate that students’ scientific argumentation skills have not yet developed fully, particularly in the aspects of reasoning and argument reinforcement. This study implies the need for adjustments to learning methods that are more targeted and sustainable to improve students’ scientific argumentation skills.